Adaptive Governance and Resilience Capacity of Farms: The Fit Between Farmers’ Decisions and Agricultural Policies - Manevska-Tasevska, Gordana; Petitt, Andrea; Larsson, Sara; Bimbilovski, Ivan; Meuwissen, Miranda P. M.; Feindt, Peter H.; Urquhart, Julie (Frontiers in Environmental Science, 2021)
Greater resilience is needed for farms to deal with shocks and disturbances originating from economic, environmental, social, and institutional challenges. Resilience can be achieved by adequate adaptive governance. This study focuses on the resilience capacity of farms in the context of multi-level adaptive governance. We define adaptive governance as adjustments in decision-making processes at farm level and policy level, through changes in management practices and policies in response to identified challenges and the delivery of desired functions (e.g. private and public goods) to be attained. The aim of the study is twofold. First, we investigate how adaptive governance processes at farm level and policy level influence the resilience capacity of farms in terms of robustness, adaptability, and transformability. Second, we investigate the “fit” between the adaptive governance processes at farm level and policy level to enable resilience. We study primary egg and broiler production in Sweden taking into consideration economic, social, and environmental challenges. We use semi-structured farmer interviews to explain the adaptive processes at farm level, and an analysis of policy documents from the Common Agricultural Policy programme 2014-2020, to explain the intervention actions taken by the Common Agricultural Policy. Results show that neither the farm level nor policy level adaptive processes on their own have the capacity to fully enable farms to be robust, adaptable, and transformable. While farm level adaptive processes are mainly directed towards securing the robustness and adaptability of farms, policy level interventions are targeted at enabling adaptability. The farm- and the policy level adaptive processes do not “fit” for attaining robustness and transformability.